Univariate spectrophotometry and multivariate calibration: Stability-indicating analytical tools for the quantification of pimozide in bulk and pharmaceutical dosage form - Amal Mahmoud Abou Al Alamein; Lobna Abd El Aziz Hussien; Ekram Hany Mohamed (Faculty of Pharmacy, Cairo University, 2015)
Simple, accurate sensitive and precise spectrophotometric and chemometric stability indicating techniques were adopted for the determination of Pimozide (PIM) in presence of its alkaline and acidic degradation products over a concentration range of 10-100 μg mL−1. The proposed spectrophotometric technique includes first derivative (D1) spectrophotometric one at 252 nm and 256.6 nm in presence of its acidic and alkaline degradates, respectively, first-derivative of the ratio spectra spectrophotometry (DR1) at 292.5 nm, the Q-analysis (absorption ratio) method, which involves the formation of absorbance equation at 242.2 nm and 281.7 nm, dual wave length method at 270.1 nm and 284 nm, the H-point standard addition method (HPSAM) and the mean centering of the ratio spectra method. The second technique is chemometric methods which include determination of PIM in presence of both its acidic and alkaline degradates using multivariate calibration methods [the classical least squares (CLS), principle component regression (PCR) and partial least squares (PLS)] using the information contained in the absorption spectra. The proposed methods have been successfully applied to the analysis of PIM in pharmaceutical dosage forms without interference from other dosage form additives and the results were statistically compared with the official method.